2016
DOI: 10.7906/indecs.14.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Panel Analysis of Internet Booking of Travel and Holiday Accommodation Indicators

Abstract: In the article four development indicators have been carefully selected and their impact on the level of acceptance of the Internet booking of travel and holiday accommodation in selected European countries has been observed. The statistical panel analysis approach was used to determine the individual and the common impact of the development indicators. The analysis has shown that an individual's wealth, the public expenditure on education, and the Internet penetration rate have a positive statistically signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The results of that phase often act as a feedback loop for the previous phases, and are particularly useful for other tourists when planning tourist trips. Dumičić et al (2016) analysed data for a 12-year period, from 2003 to 2014, based on data from Eurostat and the World Bank. First of all, the analysis showed that in the observed period there was a significant increase in the percentage of the population that booked tourist accommodation online; namely, this percentage continuously grew from a level of around 5% in 2004 to a level of around 23% in 2014, whereby the presented percentages refer to the average of the observed European countries.…”
Section: Evaluation Phase • Simple Sharing Of Experiencesmentioning
confidence: 99%
“…The results of that phase often act as a feedback loop for the previous phases, and are particularly useful for other tourists when planning tourist trips. Dumičić et al (2016) analysed data for a 12-year period, from 2003 to 2014, based on data from Eurostat and the World Bank. First of all, the analysis showed that in the observed period there was a significant increase in the percentage of the population that booked tourist accommodation online; namely, this percentage continuously grew from a level of around 5% in 2004 to a level of around 23% in 2014, whereby the presented percentages refer to the average of the observed European countries.…”
Section: Evaluation Phase • Simple Sharing Of Experiencesmentioning
confidence: 99%
“…Furthermore, several Croatian authors have analyzed internet purchases and also internet booking (Dumičić, Čeh Časni, Palić, 2014, Dumičić, Žmuk, Mihajlović, 2016. Bezić and Gašparin (2009), as the main difficulties of e-commerce implementation in Croatia at that time, mentioned difficulties related to inability of financing, staff inadequacy and the inability of hiring additional workers to maintain an ecommerce system.…”
Section: Introductionmentioning
confidence: 99%